Periodontal Disease Awareness and Knowledge among Nigerian Primary School Teachers - Azodo, CC (Ann Med Health Sci Res, 2015)
BACKGROUND: Teacher-led oral health education is equally effective in improving the oral health knowledge and oral hygiene status of adolescents as dentist-led and peer-led strategies. AIM: The aim was to determine periodontal disease awareness and knowledge among Nigerian primary school teachers. SUBJECTS AND METHODS: This cross-sectional study was conducted among primary school teachers in Edo State, Nigeria. A self-administered questionnaire which elicited information on demography, awareness of the periodontal disease and source of information, knowledge of etiology, and symptoms of the periodontal disease, was the data collection tool.. The test of association was done using either Chi-square or Fisher's exact statistics. P value was set at 0.05 for significance level. RESULTS: Out of 180 teachers recruited from seven public primary schools in Benin City, Edo State, Nigeria, 151 of them fully participated by filling the study questionnaires giving a 83.9% (151/180) response rate. The majority 74.2% (112/151) of the participants reported having heard of the periodontal disease and the leading source of information was television. A total of 29.8% (45/151) of participants considered periodontal disease as the main cause of tooth loss among adult Nigerian. Only 12.6% (19/151) of the participants knew dental plaque as soft debris on teeth and 29.1% (44/151) attested that plaque can cause periodontal disease. The majority of the participants were not aware of age 81.5% (123/151) and gender 96.7% (146/151) predisposition to periodontal disease. The perceived manifestations of the periodontal disease reported by were mainly gum bleeding 35.1% (53/151) and swollen gum 20.5% (31/151). A total of 70.2% (106/151) of the participants considered periodontal disease as a preventable disease and about half 49.0% (74/151) of the participants considered daily mouth cleaning as the best preventive method. The majority 95.4% (144/151) of the participants expressed interest in learning about the periodontal disease and the most preferred methods were workshops and lectures. CONCLUSION: A significant proportion of the participants heard about periodontal disease from nondental clinic sources. There existed a poor awareness of etiology, age and gender predispositions, manifestation, complications, and the preventable nature of periodontal disease among the participants. However, the majority of them indicated interest in learning about periodontal disease which should be utilized in optimizing their knowledge.